Fetal pleural effusion - a rare case of shunt migration - Tlemçani,Inês (2025)
Abstract Fetal pleural effusion can have various underlying causes. However, regardless of the cause, intrauterine treatment poses significant challenges and sometimes requires ultrasound-guided drainage of the effusion to reduce its volume and prevent pulmonary atelectasis. The placement of intrauterine shunts is a complex procedure that allows for the drainage of the effusion, but it is associated with potential fetal risks. There are few descriptions of complications associated with the procedure in the literature. This intriguing clinical case, illustrated with ultrasound images, demonstrates a rare complication associated with this intervention.